Heart-specific overexpression of (pro)renin receptor induces atrial fibrillation in mice. (1st April 2015) - Lian, Hong; Wang, Xiaojian; Wang, Juan; Liu, Ning; Zhang, Li; Lu, Yingdong; Yang, Yanmin; Zhang, Lianfeng
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia, causing substantial cardiovascular morbidity and mortality. The renin–angiotensin system (RAS) has been shown to be involved in the pathophysiology of AF. The (pro)renin receptor [(p)RR] is the last identified member of RAS. However, the role of (p)RR in AF is still unknown. Methods and results: Circulating levels of (p)RR were determined using an immunosorbent assay in 22 patients with AF (paroxysmal or persistent) and 22 healthy individuals. The plasma levels of (p)RR increased 3.6-fold in AF patients ( P  < 0.001), indicating a relationship between (p)RR and AF. To investigate the role of (p)RR in the regulation of cardiac arrhythmia, we generated a transgenic mouse with overexpression of human (p)RR gene specifically in the heart. Electrocardiograms from (p)RR transgenic mice showed typical atrial flutter since 2 months, then spontaneously converted to atrial fibrillation by 10 months. The atria of the transgenic mice demonstrated significant dilation and fibrosis, and exhibited a high incidence of sudden death. Additionally, the genes of SERCA and HCN4, which are involved in the electrophysiology of AF, were significantly down-regulated and up-regulated respectively in transgenic mice atria. The phosphorylation of Erk1/2 significantly increased in the atria of the transgenic mice, and the activated Erk1/2 was found predominantly in cardiac fibroblasts, suggesting that the transgenic (p)RR gene may induce atrial fibrillation by activation of Erk1/2 in the cardiac fibroblasts of the atria. Conclusions: (p)RR promotes atrial structural and electrical remodeling in vivo, which indicates that (p)RR plays an important role in the pathological development of AF. Highlights: The plasma levels of (p)RR increased in AF patients. Transgenic mouse with overexpression of (p)RR gene specifically in the heart showed typical atrial fibrillation by 10 months. (p)RR promotes atrial structural and electrical remodeling in vivo. The (p)RR may be an important gene in the pathological development of AF.